Sociodemography effect on digital financial inclusion in Indonesia: Evidence from the World Bank’s Global Findex - Nur Andriyani; Annisa Nur Salam; Siti Aisyah; Handy Nugraha (Nur Science Institute, 2025)
Digital financial inclusion is an effective and efficient measure in accelerating financial inclusion, including in Indonesia. This study aims to analyze sociodemographic factors on the probability of digital payment usage. The data used comes from the World Bank Gallup World Poll Survey 2021 on the Global Financial Inclusion Index released by the World Bank, with 1,062 respondents. By applying logistic regression, this study explores the influence of sociodemographic factors such as gender, education, income, age, place of residence, and internet access on the probability of using digital payments. The results show an imbalance in gender, with women having a higher likelihood of using digital payments. Additionally, higher education and income levels increase the likelihood of using digital payments. However, there is an inconsistency where higher income actually reduces the likelihood of using digital payment services. On the other hand, there is a disparity in opportunities between individuals living in rural and urban areas and in accessibility to the internet. The U-shaped hypothesis regarding the relationship between age and digital payment usage is proven in this study. Overall, the results show that individuals with higher sociodemographic status are more likely to use financial technology.